CMS phase-2 DAQ and timing hub prototyping results and perspectives. (1st May 2022) - Amoiridis, V.; Behrens, U.; Bocci, A.; Branson, J.; Brummer, P.; Cittolin, S.; Da Silva-Gomes, D.; Da Silva Almeida, J.; Darlea, G.-L.; Deldicque, C.; Dobson, M.; Gigi, D.; et al.
Abstract: This paper describes recent progress on the design of the DAQ and Timing Hub, or DTH, an ATCA (Advanced Telecommunications Computing Architecture) hub board intended for the phase-2 upgrade of the CMS experiment. Prototyping was originally divided into multiple feature lines, spanning all different aspects of the DTH functionality. The second DTH prototype merges all R&D and prototyping lines into a single board, which is intended to be the production candidate. Emphasis is on the process and experience in going from the first to the second DTH prototype, which included a change of the chosen FPGA as well as the integration of a commercial networking solution.